Self Disclosureof Hiv-Positive Women with Counselors at “Bahagia” Medan Social Rehabilitation Center for People with HIV (BRSODH) - Siregar, Ira Nurdewita; Mazdalifah, Mazdalifah; Nurbani, Nurbani (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2021)
This study aims to describe and analyze how the self-disclosure of women victims of HIV in conducting interpersonal communication with counselors. The research was conducted at the Center for the Social Rehabilitation of People Living with HIV (BRSODHA) "BAHAGIA" Medan. This study uses a qualitative method with a constructivism approach. The research subjects in this study were 2 (two) women HIV victims at BRSODH "Bahagia" Medan and 1 (one) triangulation informant, namely a counselor at BRSODH "Bahagia" Medan. The data collection technique used in-depth interviews, while the theories used as references in this study were the theory of interpersonal communication, self-disclosure and the theory of social penetration. Research findings show that in self-disclosure interpersonal communication, HIV victims are open about the topic of personal experiences, feelings and problems they face. Both informants admitted to telling the topic in depth but still filtering what was revealed. Both informants were afraid and embarrassed to talk about the future because they were afraid to have expectations that did not meet their expectations. Both informants tend to be more comfortable doing self-disclosure to fellow PLWH compared to counselors because of their similarity in status.